2007
DOI: 10.1080/14767050701495011
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia is associated with low concentrations of protein Z

Abstract: Objective. Protein Z, a vitamin K-dependent plasma protein, has an important role in the regulation of the coagulation cascade. Protein Z deficiency has been associated with unexplained pregnancy loss and adverse pregnancy outcome in patients with thrombophilia. This study was conducted to determine if preeclampsia (PE), small for gestational age (SGA), and fetal demise are associated with changes in maternal plasma concentrations of protein Z. Study design. This cross-sectional study included normal pregnant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 50 publications
2
34
2
1
Order By: Relevance
“…[34][35][36] In a previous study, PZ levels in pregnancies with fetal demise were found to be lower than those with healthy fetus. 26 Consistently, our study also support this findings. Because perinatal and maternal mortality is higher in more severe disease, suggested pathogenetic mechanisms for low PZ levels in HELLP syndrome would be expected to be more severe.…”
Section: Discussionsupporting
confidence: 93%
“…[34][35][36] In a previous study, PZ levels in pregnancies with fetal demise were found to be lower than those with healthy fetus. 26 Consistently, our study also support this findings. Because perinatal and maternal mortality is higher in more severe disease, suggested pathogenetic mechanisms for low PZ levels in HELLP syndrome would be expected to be more severe.…”
Section: Discussionsupporting
confidence: 93%
“…1 Progressive rise of the median PZ level (lg/ml) in the first (n = 15), second (n = 97) and third (n = 66) trimester of pregnancy stable throughout pregnancy and the PZ deficiency could not be explained by gestational age. Erez et al found that the median concentration of PZ was reduced in pre eclampsia but not in women who delivered small for gestational age babies [9]. However, our results clearly show that the PZ levels rise progressively during the three trimesters and that this rise is blunted in patients with adverse pregnancy outcome or an associated pregnancy complication like preeclampsia or diabetes ( Fig.…”
Section: Discussioncontrasting
confidence: 51%
“…However, our results clearly show that the PZ levels rise progressively during the three trimesters and that this rise is blunted in patients with adverse pregnancy outcome or an associated pregnancy complication like preeclampsia or diabetes ( Fig. 1; Tables 3, 4) PZ is suggested to be a physiologic down regulator of blood coagulation and low PZ levels are associated with increased risk of ischemic stroke, particularly in males even in the absence of diabetes [9]. The levels of PZ in diabetic pregnant women has not been studied at all in the past and our results show that the median PZ levels in pregnant women with diabetes were comparatively the lowest amongst the subsets of pregnant subjects but did not reach statistical significance due to the small sample size (n = 18).…”
Section: Discussionmentioning
confidence: 59%
“…While ZPI may inactivate Xa by itself, its binding to PZ increases its activity by 1,000-folds [18,19]. Reduction in PZ levels induces a procoagulant state and is associated with thrombotic diseases, including ischemic stroke, cardiovascular diseases [19], and pregnancy complications [14,20].…”
Section: Introductionmentioning
confidence: 99%